THREE FACTOR MODEL DAN KEPEMILIKAN ASING TERHADAP TINGKAT RETURN - Richard Irawan; Werner R. Murhadi (Journal of Management and Business, 2012)
Indonesian government issued various regulations and policies of market liberalization and provide the widest opportunities both local and foreign investors to trade. Stock market liberalization should improve market efficiency is similar to the stock markets of developed countries. Intensive research conducted by Fama and French succeeded in explaining the performance of stocks in developed countries with three factors model approach. This study tried to model the stock markets of Indonesia and the added factor of foreign ownership is considered by some to dominate price movements. This study used a sample of 269 firms from 2008 to 2011 period. The study uses panel data regression. The results showed the market factor, size and book-to-market has a positive effect on returns while foreign ownership factors do not affect significantly.